Pneumatologia w isagodze Juniliusza Afrykańczyka - Czyżewski, Bogdan Stanisław (Verbum Vitae, 2020)
The work of the ancient author Junilius Africanus (6th century), Instituta regularia divinae legis, is an interesting introduction (isagoge) to the study of the Holy Scriptures. It not only organizes the canon of the Old and New Testaments, but also contains concise interpretations of some of the biblical texts. Among many other doctrinal questions, Junilius deals in his biblical textbook with pneumatology. It presents pneumatology through a double perspective. First, the Holy Spirit is defined as the grece, that He is himself, because He gives himself as a gift to man. The second theme shows both the unity of the Holy Spirit with the Father and the Son and also the separateness of the Divine Persons, in the Trinitarian perspective.